China's emerging Arctic engagements: Should India reconsider its approach towards the polar north?. (2nd January 2020) - Sharma, Bipandeep
ABSTRACT: Climate induced geo-physical transformations occurring in the Arctic are also attributing to geopolitical transformations of the region. Opening up of the Arctic is resulting in a geopolitical race amongst the Arctic and non-Arctic states to dominate emerging economic and strategic opportunities in the region. Transformations in the Arctic assume global links and possess a potential of significantly impacting the Arctic as well as the Asian states. China's assertiveness to become a Polar Great Power has set a course for new Asian perceptions towards the region. In pursuits of its economic, environmental, scientific, social and strategic endeavours, China is making significant inroads in the region to meet its short and long-term objectives. This paper makes an attempt to reconsider India's approach towards the Arctic not by taking China as a benchmark, but rather as a useful backdrop to broaden and deepen India's engagements in the circumpolar north.